1999
DOI: 10.1093/humrep/14.3.842
|View full text |Cite
|
Sign up to set email alerts
|

The contribution of maternal serum markers in the early prenatal diagnosis of molar pregnancies

Abstract: The aim of this study was to evaluate the usefulness of maternal serum markers in the early prenatal diagnosis of molar pregnancies. The ultrasound features, cytogenetic and histopathological findings of 10 cases of molar pregnancy diagnosed at 11-13 weeks of gestation were compared retrospectively with the maternal serum concentrations of human chorionic gonadotrophin (HCG), alpha fetoprotein (AFP), pregnancy-associated plasma protein A (PAPP-A) and pregnancy-specific beta1-glycoprotein (SP1). Free beta-HCG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…A complete hydatidiform mole with a coexisting normal fetus was diagnosed in one of our cases and was reported earlier by our group and others [20][21][22] .…”
Section: Discussionsupporting
confidence: 81%
“…A complete hydatidiform mole with a coexisting normal fetus was diagnosed in one of our cases and was reported earlier by our group and others [20][21][22] .…”
Section: Discussionsupporting
confidence: 81%
“…However, diagnosis in the first trimester is more difficult owing to the reduced extent of hydropic change, with sonographic diagnosis of CHM more likely than PHM; in the first trimester, around 80% of CHM is detectable by pre‐evacuation sonography, compared to only about 30% of PHM81–87. Before 13 weeks' gestation some PHM may appear as an enlarged placenta without or with only scanty vesicular changes88–92. Since the introduction of routine first‐trimester ultrasound examination, HMs have been evacuated at earlier gestations (current average 9–10 weeks in the UK), before the stage of development at which they have the classical morphological features, and revised diagnostic histological criteria are now required for their histopathological diagnosis93–95.…”
Section: Placental Malignancymentioning
confidence: 99%
“…At that point it was difficult to distinguish between a spontaneous abortion and molar pregnancy. Recently, Jauniaux et al [14] reported the contribution of maternal serum markers to the early prenatal diagnosis of molar pregnancy. Based on the combination of hCG titer and ultrasonographic findings, we suspected molar pregnancy on Day 18 after the first visit.…”
Section: Resultsmentioning
confidence: 99%